Potential Shariah Non-compliance Practices In E-bidding: Observation From E-bidding Platforms In Malaysia - Muhamad Azhari Wahid; Khairil Faizal Khairi; Hamdi Hakeim Mudasir; Muhammad Farid Hadhari Mahamed Rusdi; Azuan Ahmad; Mohd Zakhiri Md Nor; Azrul Azlan Iskandar Mirza (USIM Press, 2024)
VOL.19 NO. 1 (JUNE) 2022 Page (120-139)